Upaya Meningkatkan Keaktifan dan Hasil Belajar Matematika Materi PLDV Melalui Penerapan Model Pembelajaran CTL - Alhasra Idawani (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research method is Classroom Action Research which is conducted in two cycles, with the explanation of each cycle consisting of two meetings by applying the CTL (Contextual Teaching and Learning) learning model. The purpose of this research is to increase the activity and learning outcomes of students in learning mathematics. The action taken is to apply the CTL (Contextual Teaching and Learning) learning model. The cycle in this study consists of several steps including planning, action, observation, and reflection. Data collection techniques in this study are observation, tests, documentation. Data analysis in this study is observational data, learning outcome data. The application of the CTL (Contextual Teaching and Learning) learning model can increase student activity in learning activities. It can be proven that active learning has increased from the initial conditions of 6 students or 27.27%, cycle I there are 13 students or 59.09%, and in cycle II there are 20 students or 90.91%. Student learning outcomes in the initial study were only 56.36 to 65.00 and 75.00 in the second cycle, with a learning completeness level of 4 students or 18.18%, cycle I there were 10 students or 45.45%, and in cycle II there were 19 students or 86.36%, although there are still 3 students (13.64%) who have not completed it yet because all the criteria for the success of the learning process have been achieved in the second cycle it is stated that the process of improving learning is complete and successful in the second cycle.